Prevention of cervical cancer: early detection of precancerous lesions of cervix in women from a marginalized environment - Christe, D. M.; Chandrasekar, Anjalakshi; Jayashree, K.; Meenalochani, P.; Gunasingh, Shaanthy T. K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The objective of the present study was to find out the efficacy of low-cost methods, available for screening for cervical cancer and early detection of precancerous lesions, of cervix. Methods: The study with power above 80%, was conducted over a period of almost three years. Women aged below fifty years were included in the study. A total of 100 women were diagnosed with cervical intraepithelial neoplasia (CIN) and 244 women with chronic cervicitis by histopathological examination reports. Ten women were HIV positive. Results: Low cost screening tests of visual inspection of cervix after application of 5% acetic acid (VIA) and visual inspection of cervix after application of Lugol’s iodine (VILI) were positive in 75% of women with CIN and in combination with colposcopy, positive in 93%. The diagnostic accuracy of colposcopy was highest at 86%. (Odds ratio-.48.79). Conclusions: Initial screening for younger women with fewer years of exposure, the low cost tests, VIA / VILI could be used under low magnification. Colposcopy should be done for all women with positive tests. The costlier human papilloma virus (HPV) tests should be done at cost effective purpose for high risk groups and when indicated, for early detection of precancerous lesions of cervix and prevention of cervical cancer.